Self-Esteem as a Mediator of Social Support and Health on Grandparents' Subjective Well-Being - Yupi, Emamiridya Erine; Lestari, Sri (Universitas Islam Indonesia, 2025)
The elderly population in Indonesia and childcare are associated with subjective wellbeing (SWB) of grandparents. On the other hand, achieving SWB is important for living a mentally healthy life. Therefore, this research aimed to predict grandparents SWB through social support, physical health, and self-esteem. A quantitative correlational method was used with 350 respondents aged 45-75 years obtained by simple random sampling technique. Data collection used four instruments, including the SWB, social support, health status, and self-esteem scale, while data analysis was performed with path analysis. The results showed that social support, health, and self-esteem affected grandparents SWB directly and indirectly. The indirect path of self-esteem as a mediator contributed more than the direct path of social support and health status. The implication of this research is to improve grandparents SWB by strengthening intergenerational relationships as a form of providing meaningful social support. This offers opportunities for grandparents to contribute to the family and community, participate in various social activities, and easily access health facilities.